Environmental risks perception, evaluation and management - Böhm, Gisela, 1962- (Amsterdam ; New York : Elsevier/JAI, 2001)
Environmental risks are among the most serious challenges of today's societies. Virtually all environmental risks are anthropogenic. The consequences of past decisions made by individuals, business, and governments have already devastated many of the earth's ecological systems and there is an ongoing discussion about the potential effects of environmental change and whether the earth will still provide a livable environment for future generations. The past decade has seen a dramatic growth in publications that focus on environmental issues. However, this literature has been dominated by the natural sciences and research focuses on obtaining more accurate information about natural and ecological processes, with the tacit assumption that this information will prove useful to improve individual, organizational, and societal decision making. This volume focuses on the psychological, sociological, and cultural aspects of environmental risks that have not been given adequate and integrated attention in the past. Understanding of the psychological, social, cultural, and political forces will determine the successes and failures of environmental risk management. In particular, public policy could be improved by the integration of more accurate assumptions about people's cognitions, attitudes, and emotions towards environmental risks.
Environmental risks -- perception, evaluation and management : introduction / Gisela Böhm ... [et al.] -- Mental representation of global environmental risks / Gisela Böhm and Hans-Rüdiger Pfister -- Communicating health risks of global climate change / Ann Bostrom and Baruch Fischhoff -- Environmental risk in the media : modelling the reactions of the audience / Josef Nerb, Hans Spada and Katja Lay -- Risk, responsibility and recreancy / William R. Freudenburg -- Attitudes, decisions and perceptions of risk : a social psychological analysis / J. Richard Eiser -- Moral dimensions in risk evaluation / Lutz H. Eckensberger, Thomas Döring and Heiko Breit -- "God will send us the fish" -- perception and evaluation of an environmental risk in Ha'apai, Tonga / Andrea Bender -- Risk and culture in the Andes : differences between indigenous and western developmental perspectives / Barbara Göbel -- Environmental risk, public trust and perceived exclusion from risk management / Lynn J. Frewer -- Value-focused thinking for environmental risk consultations / Robin Gregory, Joseph Arvai and Tim McDaniels -- Environmental risks -- perception, evaluation and management : epilogue / Ortwin Renn and Andreas Klinke.
Includes bibliographical references.
Description based on print version record.
Keywords: Environmental risk assessment; Offenses against the environment; Social impact of environmental issues; Political Science -- Public Policy -- Environmental Policy